1972
DOI: 10.1159/000197286
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Gastric Mucous Secretions in Man by Secretin

Abstract: Gastric mucous secretions were collected in fasting patients following a careful gastric washout. The stomach, perfused with saline, was continuously reaspirated. Saliva was obtained separately during the test. Gastric and salivary secretions were collected in four successive 30-min samples. Saline was infused intravenously, alone during the first control period, associated to various doses of secretin during the three following periods: 0 U/kg/h (control series); 0.125 U/kg/h (series II); 0.395 U/kg/h (series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1973
1973
1992
1992

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Since we did not try to eliminate duodenal reflux of bile or pancreatic juice and saliva swallowing from GF, the results obtained in HP in which no contamination can occur, are more reliable. With careful collection of gastric juice in man, using a gastric infusion-aspiration system, the effect of secretin has been confirmed in the innervated stomach [1],…”
Section: Discussionmentioning
confidence: 99%
“…Since we did not try to eliminate duodenal reflux of bile or pancreatic juice and saliva swallowing from GF, the results obtained in HP in which no contamination can occur, are more reliable. With careful collection of gastric juice in man, using a gastric infusion-aspiration system, the effect of secretin has been confirmed in the innervated stomach [1],…”
Section: Discussionmentioning
confidence: 99%
“…Secretin produced stimulation of both glycoprotein and polysaccharide fractions (8,9). André et al (7) found, in man, that secretin induced a sustained increase in the output of fucose, galactose, total hexosamines, uronic acid and sulfate. They did not use pentagastrin but assessed the effect of secretin on nonstimulated gastric secretion (7).…”
Section: Discussionmentioning
confidence: 99%
“…André et al (7) found, in man, that secretin induced a sustained increase in the output of fucose, galactose, total hexosamines, uronic acid and sulfate. They did not use pentagastrin but assessed the effect of secretin on nonstimulated gastric secretion (7). Previous studies (7 -9 ) did not use the gas chromatography procedure for analysis of mucinous components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secretin increases gastric mucous secretion in man [1] and the cat [12] but not in the dog [13] and the rat [11]. One may assume that species dif ferences could atïect the physiology of gastric glycoproteins.…”
Section: Discussionmentioning
confidence: 99%